2003
DOI: 10.1002/ajmg.a.20130
|View full text |Cite
|
Sign up to set email alerts
|

Case‐control study of cleft lip or palate after maternal use of topical corticosteroids during pregnancy

Abstract: A case-control survey of 48 children with nonsyndromic cleft lip or palate showed a significant increase in prevalence of maternal use of topical corticosteroid preparations in the first trimester of pregnancy, compared to 58 controls born in the same hospital; the odds ratio was 13.154, 95% confidence interval 1.67-586, P = 0.0049 on Fisher's exact two-tail test. The results were statistically significant although the wide confidence interval reflected the small sample size. Although older epidemiological stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 33 publications
(27 reference statements)
1
52
0
Order By: Relevance
“…Studies specifically evaluating topical corticosteroids and orofacial clefts are uncommon. [4][5][6]8,9 A recent Cochrane review of the safety of topical corticosteroids during pregnancy concluded that the current studies were limited and inconclusive and that cohort studies with very large samples were needed. 33 …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies specifically evaluating topical corticosteroids and orofacial clefts are uncommon. [4][5][6]8,9 A recent Cochrane review of the safety of topical corticosteroids during pregnancy concluded that the current studies were limited and inconclusive and that cohort studies with very large samples were needed. 33 …”
Section: Discussionmentioning
confidence: 97%
“…[3][4][5][6][8][9][10] However, many of the previous studies were limited by a lack of statistical power. The largest study to date, an American case-control study, included 39 instances of orofacial clefts associated with exposure to corticosteroids, 4 whereas our study included 84 instances associated with exposure during the first trimester.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigations have reported that the use of corticosteroids during early pregnancy is associated with a 3-to 6-fold increased risk of orofacial clefts. [71][72][73][74][75] Although systemic corticosteroids are associated with a higher risk of orofacial clefts than topical corticosteroids, the latter is not without risk. It has been shown that application of hydrocortisone cream on eczematous skin is associated with significant increase in the level of plasma cortisol.…”
Section: Maternal Corticosteroid Use and The Risk Of Orofacial Cleftsmentioning
confidence: 99%
“…[76] In a study by Edwards et al, a significant association between topical corticosteroids and orofacial cleft was observed. [77] Epidemiologic data have shown that low-to-moderate doses of inhaled corticosteroids taken during the first trimester of pregnancy are safe but raise concerns about high doses. [78] The mechanism of cleft palate production by corticosteroids is uncertain; it is a complicated interference in a complex developmental program involving many genetic and biochemical processes.…”
Section: Maternal Corticosteroid Use and The Risk Of Orofacial Cleftsmentioning
confidence: 99%